Bibliometrics Contribution to the Metatheoretical and Domain Analysis Studies - Gutierres Castanha, Renata Cristina [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Ergon-verlag, 2014)
Along with the growth of scientific production, the bibliometric studies have become essential, providing relevant information about any domain while identifying, highlighting and viewing the scientific knowledge constructed within a theme, subject or knowledge area. This article approaches the bibliometric studies under the light of metatheory and domain analysis within the knowledge organization in information science. domain analysis and metatheory are considered significant contribution to bibliometric studies when emphasizing the need for epistemological, sociological and historical analyzes, as well as other qualitative approaches, encouraging researchers to reflect on the whole composition of the research object, by means of different methodological, theoretical and epistemological approaches. This study aims at contributing to the discourse of the theoretical aspects of bibliometric studies by presenting considerations concerning Hjorland's domain analysis, as well as Ritzer's metatheoretical approach, featuring discussions on major theories of a study field, since these approaches together provide a more complete qualitative view upon an area, here, represented by the bibliometric studies.
Keywords: knowledge; theory; domain analysis; information science; metatheory